Extended pterional approach with orbital flattening for suprasellar and parasellar lesions - Gasser H.R Al-Shyal (Wolters Kluwer Medknow Publications, 2021)
Background and aim The aim of this study was to investigate the advantages of the extended pterional approach and compare it with more invasive and less-invasive similar approaches. Patients and method s This study is an observational retrospective case-series study and descriptive statistics was used. Twelve patients with suprasellar and parasellar lesions were managed in the period between January 2016 and January 2019. Preoperative and postoperative clinical and radiological assessment were done for each patient. Results Twelve cases were done via this approach. There were nine females and three males. Age ranges from 2 to 55 years with a mean of 31.7 years. Regarding pathology, eight (67%) cases were meningiomas, three (25%) cases were craniopharyngiomas, while one (8.3%) case was pituitary adenoma. Most of the cases (91.7%) were presented with visual affection. The lesion was excised totally (gross total resection) in seven (58.3%) out of the 12 cases. Visual affection improved in seven (63.6%) out of 11 cases. Regarding complications, one case experienced permanent hemiparesis. One patient had deep-vein thrombosis that had been treated. One case had seizures. Approach-related complications: two cases had periorbital edema that disappeared within 1 week. One case had a rim of subdural hematoma. Frontalis nerve injury occurred in two cases, one of them improved within 6 months. We do not have a permanent cosmetic deformity with this approach. Conclusion The extended pterional approach has less functional and cosmetic complications and it can be done in lesser time than frontotemporal-orbitozygomatic approach. The exposure is much larger than conventional pterional approach.